MTOR signaling in immune cells and its implications for cancer immunotherapy. (1st November 2017) - Zeng, Hu
Abstract: The realization that cellular metabolism dictates immune cell development, differentiation and function affords metabolic intervention as a potential venue for cancer immunotherapy. mTOR signaling, as a metabolic master regulator, controls immune cell biology in a cell type-specific and context dependent manner. Furthermore, mTOR activity needs to be fine-tuned to maintain proper immune function. These properties may be exploited for therapeutic purpose, yet caution should be taken against radical changes of mTOR activity. Here, the intricate and complex mTOR regulation in different immune cells is reviewed, highlighting latest discoveries and opportunities for cancer immunotherapy. Highlights: Only a modest reduction of mTORC1 activity bolsters memory CD8 + T cells. Proper Treg function requires optimum level of mTOR activity. mTOR controls myeloid cell homeostasis and function in a context dependent manner. Targeting mTOR for cancer immunotherapy requires tailored optimization.